2015
DOI: 10.1007/s10143-015-0636-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the globus pallidus internus or ventralis intermedius nucleus of thalamus for Holmes tremor

Abstract: Holmes tremor (HT) is a difficult-to-treat, very disabling symptomatic condition which characteristically appears weeks to years after a brain lesion. It features a unique combination of rest, action, and postural tremors. Pharmacotherapy is mostly not effective. Chronic deep brain stimulation (DBS) of ventralis intermedius nucleus (Vim) of thalamus has been described as being the best surgical approach in singular case series; various authors observe, however, cases with partial responses only; therefore, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 49 publications
0
26
0
1
Order By: Relevance
“…All but one study reported no occurrence of AEs, and 1 study did not report AEs. Stimulation frequency ranged from 130 to 185 Hz, intensity from 2.0 to 6.0 V, and pulse width from 90 to 210 sec (Table 1) [26, 30, 3537]. …”
Section: Resultsmentioning
confidence: 99%
“…All but one study reported no occurrence of AEs, and 1 study did not report AEs. Stimulation frequency ranged from 130 to 185 Hz, intensity from 2.0 to 6.0 V, and pulse width from 90 to 210 sec (Table 1) [26, 30, 3537]. …”
Section: Resultsmentioning
confidence: 99%
“…However, satisfactory clinical improvement following treatment with L -dopa is not achieved in some patients, as in our case, and other oral medications, botulinum toxin injections,27,28 or several surgical procedures are required 29,30…”
Section: Discussionmentioning
confidence: 61%
“…e Ic, a region of the limbic system, can change the genioglossus tension, as well as the breathing depth and rate. Many neurotransmitters regulating the limbic system are associated with many diseases [20][21][22][23]. Signals propagating from the Ic to the Hb could reduce the release of 5-HT in the raphe nuclei.…”
Section: Discussionmentioning
confidence: 99%